ANALISIS USAHATANI SAGU (Metroxylon sagu Rottb.) .DI KABUPATEN LUWU UTARA, SULAWESI SELATAN - Manambangtua, Alfred Pahala (Jurnal Sosial Ekonomi Pertanian, 2020)
Sago is a palm plant that can be used as a pith on the stems into flour. Sago has potential as an alternative food source because it contains a high carbohydrate content. Sago plants have many advantages over other carbohydrate-producing plants, because they can be harvested at any time regardless of the season. The results showed that. Sago farmers in North Luwu District monthly income of Rp. 109.349,- and Rp. 1.312.186,- per year. Calculation Analysis of R / C Ratio of sago farmers in Nort Luwu is 4,14, under the condition if the value of R / C Ratio> 1 then the work done can be profitable and worth trying.